Seasonal Variability and Underlying Dynamical Processes of Sea Surface Temperature Fronts in Zhoushan and Its Adjacent Seas - Hui Chen; Qiyan Ji; Qiong Wu; Tengteng Peng; Yuting Wang; Ziyin Meng (Journal of Marine Science and Engineering)
The oceanic fronts play an important role in marine ecosystems and fisheries. This study investigates the seasonal variability of sea surface temperature (SST) fronts in Zhoushan and its adjacent seas for the period 1982–2021. The influences of various underlying dynamic processes on the fronts are also discussed. The horizontal gradient of SST is calculated as frontal intensity, and a threshold value of 0.03 °C/km is set to count the frontal frequency. The fronts in Zhoushan and its adjacent seas show significant seasonal variability, with high (0.1 °C/km and 60–90%) and low (0.03 °C/km and 30–60%) frontal activity in winter and summer, respectively. In summer, the fronts along Jiangsu and the north of the Changjiang River Estuary show higher frontal intensity and frequency, which is mainly influenced by the Changjiang diluted water and southerly wind, and fronts around Zhoushan Island are highly related with Zhoushan upwelling. In winter, the fronts strengthen into regular bands offshore and parallel to the coast, which are mainly influenced by coastal currents. Frontal intensity and frequency show a more significant long-term increasing trend in winter than in summer.